Connecting Caregivers to Support: Lessons Learned From the VA Caregiver Support Program. (April 2020) - Bruening, Rebecca; Sperber, Nina; Miller, Katherine; Andrews, Sara; Steinhauser, Karen; Wieland, G. Darryl; Lindquist, Jennifer; Shepherd-Banigan, Megan; Ramos, Katherine; Henius, Jennifer; Kabat, Margaret; Van Houtven, Courtney
Development and evaluation of supportive caregiver interventions has become a national priority. This study's aim was to evaluate how caregivers participating in the Department of Veterans Affairs (VA) Caregiver Support Program (CSP) use and value supportive services. Qualitative semi-structured interviews ( N = 50 caregivers) were the core of a mixed-methods design, and surveys ( N = 160) were supplemental. Caregivers who had used CSP services valued emotional, functional, and health care navigational support, calling support groups and the program coordinator their "lifeline." However, many described a lack of connection with the program—not knowing about or successfully engaging in program services—and needed more information about available resources. Caregivers in rural areas or caring for individuals with specific diseases reported needing tailored services to meet their unique needs. Policy makers and practitioners should proactively promote supportive services for caregivers. Future research should explore strategies for reducing barriers to accessing tailored support to meet the needs of a diverse caregiver population.